Handwashing Practices and Its Predictors Among Primary School Children in Damote Woide District, South Ethiopia: An Institution Based Cross-Sectional Study. (March 2022) - Admasie, Amha; Guluma, Alemu; Feleke, Fentaw Wassie
Background: Handwashing in schools with soap could substantially reduce diarrhea and respiratory infections among school-age children; however, in low-and-middle-income countries, handwashing is still being practiced to a very low extent in particular critical moments such as before eating and after using the toilet. Therefore, the main objective of this study was to assess the level of handwashing practice and its predictors among primary school children in South Ethiopia. Methods: A school-based cross-sectional study was conducted using a multistage cluster sampling technique from 6 primary schools with 580 students in total. Schools were purposively selected and the students were random. Data were collected using pre-tested questionnaires administered by interviewers and trained data collectors. Data were entered using Epi Data and exported to SPSS software for analysis. Both bivariate and multivariable logistic regression analyzes were used. Result: Proper handwashing practice was reported in 28.10% (95% CI, 24.5, 31.7%) of students. Being eighth grade (AOR = 3.44, 95% CI 1.52, 8.23), urban residence (AOR = 18.84, 95% CI 14.02, 23.29], having parents (AOR = 10.74; 95% CI 8.80-12.36), role model teachers (AOR = 6.45; 95% CI 5.52-8.99), role model health professionals (AOR = 9.62; 95% CI 2.70-14.19), and school handwashing facility (AOR = 3.84, 95% CI 3.60, 4.07) were predictors of proper handwashing practice. Conclusions: Proper handwashing practice among schoolchildren was found below. Therefore, promoting and improving handwashing practices and preparing handwashing facilities in schools is mandatory to address the handwashing practice gap among primary school students in the study area.